2019
DOI: 10.3389/fmicb.2019.01051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proinflammatory Cytokines on the Virulence of Uropathogenic Escherichia coli

Abstract: The effect of a urinary tract infection on the host is a well-studied research field. However, how the host immune response affects uropathogenic Escherichia coli (CFT073) virulence is less studied. The aim of the present study was to investigate the impact of proinflammatory cytokine exposure on the virulence of uropathogenic Escherichia coli. We found that all tested proinflammatory cytokines (TNF-α, IL-1β, IL-6, IL-8 and IFN-γ) induced an increased CFT073 growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The pro-inflammatory cytokine-mediated mechanism of bacterial growth augmentation involves a direct interaction between cytokines and bacterial cells. For example, addition of TNF-α, IL-1 β, IL-6, IL-8 and IFN-γ cytokines (from commercial sources) in bacterial growth medium triggered a rapid growth of uropathogenic E. coli strain CFT073, possibly by increasing iron acquisition by the bacterium ( Engelsoy, Rangel & Demirel, 2019 ). Type I IFNs are also directly involved in dysbiosis induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-inflammatory cytokine-mediated mechanism of bacterial growth augmentation involves a direct interaction between cytokines and bacterial cells. For example, addition of TNF-α, IL-1 β, IL-6, IL-8 and IFN-γ cytokines (from commercial sources) in bacterial growth medium triggered a rapid growth of uropathogenic E. coli strain CFT073, possibly by increasing iron acquisition by the bacterium ( Engelsoy, Rangel & Demirel, 2019 ). Type I IFNs are also directly involved in dysbiosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…Avian influenza viruses are among the numerous pathogens that induce strong innate immune responses such as IFNs and pro-inflammatory cytokines ( Akira, Uematsu & Takeuchi, 2006 ; Medzhitov & Janeway Jr, 2000 ; Mogensen, 2009 ) which can trigger dysbiosis in the respiratory tract of mammals ( Duvigneau et al, 2016 ; Engelsoy, Rangel & Demirel, 2019 ; Madouri et al, 2018 ; Sharma-Chawla et al, 2019 ) and in the avian gut ( Ganz et al, 2017 ; Hird et al, 2018 ; Li et al, 2018 ; Yitbarek et al, 2018c ; Zhao et al, 2018 ). However, influenza virus-induced dysbiosis of avian respiratory microbiota has not been described due to challenges in respiratory sampling methodologies ( Abundo et al, 2020 ; Abundo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nematode Caenorhabditis elegans has been used for in vivo infection studies that include various UTI pathogens (Lavigne et al, 2008;Szabados et al, 2013;Engelsöy et al, 2019). Very recently, Hashimoto et al demonstrated that UPEC mutants with defective iron acquisition-related virulence factors were a significant factor in survival of C. elegans (Hashimoto et al, 2021).…”
Section: Other Animal Models For Utimentioning
confidence: 99%
“…The nematode Caenorhabditis elegans has been used for in vivo infection studies that include various UTI pathogens ( Lavigne et al., 2008 ; Szabados et al., 2013 ; Engelsöy et al., 2019 ). Very recently, Hashimoto et al.…”
Section: Animal Models For Studying Utimentioning
confidence: 99%
“…These cytokines are important for the clearance of UPEC and the recruitment of neutrophils. 5 Human C-X-C ligand 8 (IL-8) is the major chemokine for neutrophil recruitment during UTI, which is secreted by the urothelial cells. 6 The level of IL-8 was also raised in the urine of humans suffering from acute UTI.…”
Section: Introductionmentioning
confidence: 99%